2014
DOI: 10.3390/ijms151221980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Platelet-Rich Plasma and Bioactive Glass Powder for the Improvement of Rotator Cuff Tendon-to-Bone Healing in a Rabbit Model

Abstract: To test the hypothesis that a platelet-rich plasma (PRP) plus bioactive glass (BG) mixture could shorten the tendon-bone healing process in rotator cuff tendon repair, thirty mature male New Zealand white rabbits were randomly divided into three groups, Control, PRP, and PRP + BG. All groups underwent a surgical procedure to establish a rotator cuff tendon healing model. Mechanical examinations and histological assays were taken to verify the adhesion of the tendon-bone. Real-time PCR was adopted to analyze Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“… 57 Besides, a previous study reported that BG can improve the integration between tendon and bone in rotator cuff tendon repair. 58 Therefore, we speculated that BG may contribute to tendon tissue healing, and our results demonstrated that delivering BG via an injectable hydrogel could be a promising therapeutic option.…”
Section: Discussionmentioning
confidence: 75%
“… 57 Besides, a previous study reported that BG can improve the integration between tendon and bone in rotator cuff tendon repair. 58 Therefore, we speculated that BG may contribute to tendon tissue healing, and our results demonstrated that delivering BG via an injectable hydrogel could be a promising therapeutic option.…”
Section: Discussionmentioning
confidence: 75%
“…Studies using rotator cuff repair models reported controversial results, ranging from no improvements [33] or detrimental effects on cell density and vascularization [22], to the amelioration of histological appearance [31, 64] and fibers organization [31]. Studies involving injury at the enthesis consistently reported improvements in terms of reduced inflammation and vascularity, [49] deposition of type I and type II collagen [126], fibers organization [115] and histologic appearance [127] following blood‐derived products application. Only one study reported a detrimental effect of platelet‐rich fibrin matrix on tissue healing with formation of fibrotic tissue [50].…”
Section: Resultsmentioning
confidence: 99%
“…The expression of the growth factors TGFβ and IGF, as well as the tendon specific marker TNMD, is increased in the first phases of tendon healing in treated animals, whilst they all decreased at later time‐points [47, 60, 73–75]. In a model of rotator cuff tear, an increase in BMP‐2 after treatment, possibly benefitting the healing of the bone‐tendon interface was reported [115].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation